Produção de atlas municipais no Brasil: estado do conhecimento - Santana, Rodrigo Bozzola de Castro e (Universidade Federal de São Carlos, 2024)
Maps have been fundamental throughout history for representing space, making the interpretation of locations more effective. Beyond simple static images, they are configured as tools capable of contextual reading. In the educational sphere, school atlases play a crucial role in the teaching of Geography, constituting valuable learning tools. Adopting the state of knowledge approach, a survey of publications on municipal school atlases in Brazil was conducted using the CAPES Theses and Dissertations Catalog and the descriptors "atlas + escolares", resulting in 15 works after a careful filtering process. The analysis of the works demonstrated the breadth of themes addressed by researchers, ranging from teacher training to innovative proposals such as Digital Atlases and the interface between Geography and cinema. The convergence around the concept of place was observed in several studies, while others explored themes such as the evolution of basic education in Brazil and the positive impact of municipal electronic Atlases. The use of municipal atlases in schools stands out as a significant resource for teaching, highlighting its adaptability, innovation, and formative potential. However, there are challenges, such as the scarcity of regional materials and the need for effective integration into the curriculum, emphasizing the importance of collaboration between researchers and educators. Gaps in research were identified, such as the multidisciplinary approach to the use of atlases, the evaluation of the impact of their use on students, the exploration of emerging technologies such as augmented reality, and sustainable strategies for continuous use. This research contributes not only to the current understanding of works on municipal school atlases but also points to promising directions for improvement and investigation in the field of the study of municipal school atlases in education.
Production of municipal atlases in Brazil: state of knowledge
Producción de atlas municipales en Brasil: estado del conocimiento
Keywords: Cartografia escolar; School cartography; Atlas escolares; Lugar; Educação; School atlases; Place; Education; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA